Advances and potential of omics studies for understanding the development of food allergy - Sindher, Sayantani B.; Chin, Andrew R.; Aghaeepour, Nima; Prince, Lawrence; Maecker, Holden; Shaw, Gary M.; Stevenson, David K.; Nadeau, Kari C.; Snyder, Michael; Khatri, Purvesh; Boyd, Scott D.; Winn, Virginia D.; et al. (Frontiers in Allergy, 2023)
The prevalence of food allergy continues to rise in the Western world, carrying with it substantial safety, economic, and emotional burdens. Although preventative strategies do exist, the heterogeneity of allergy trajectories and clinical phenotypes has made it difficult to identify patients who would benefit from these strategies. Therefore, further studies investigating the molecular mechanisms that differentiate allergic trajectories are needed. Large-scale omics studies have identified key insights into the molecular mechanisms for many different diseases, however the application of these technologies to uncover the drivers of food allergy is in its infancy. Here we review the use of omics approaches in food allergy and highlight key gaps in knowledge for applying these technologies for the characterization of food allergy development.